Diseño y construcción de un sistema prototipo para oxigenación del agua mediante energía solar para la Laguna Daniel Álvarez de la ciudad de Loja. - Jimbo Jaramillo, Oscar Alexis (2011)
The present thesis work was centered in the design and construction of a system prototype for oxygenation of the water by means of solar energy for the Lagoon Daniel Álvarez of the City of Loja. For the design of the thesis a well structured methodology was used, taking as starting point the mathematical pattern developed by Eckenfelder Jr and O`Connor, besides diverse bibliography that allowed us the calculation of the panel, of the battery, of the load controller, and the selection of the relays, the pressure switch and the electro valve. Based on the design of the thesis the aerator of water was built by means of diffusion of bubbles with energy supply starting from a photovoltaic system. They were carried out two analysis of the raw and treated water of the lagoon Daniel Álvarez, both analyses were carried out them in the UMAPAL, starting from that which was obtained results of the parameters so much physical-chemical as microbiological of the raw and treated water. It was determined in the first physical analysis - chemical that there was an increase of the level of pH in 5% in the treated water, of the turbidity in 12%, of the solids suspended in 15% and the sulphides in 64%, and there was a reduction in the color in 7%, in the total alkalinity in 45%, of the DQO in 31%, of the electric conductivity in 33%, of the chlorides in 63% and of the sulfates in 100%, all these data in connection with the obtained values of the raw water. A second analysis of the water of the lagoon the one was made which was oxygenated by the aerator of water by means of diffusion of bubbles that you builds, the sample of this analysis was of about 8000 ml and I am carried out it in the UMAPAL, starting from that which was obtained results of the physical so much analyses - chemical as microbiological of the raw and treated water. Basing us in these analyses, it could be proven that the water of the lagoon is polluted with a great quantity of substances and harmful microorganisms, and that the aeration process carried out through the system prototype for oxygenation of the water by means of solar energy that was built, not allows the reduction in its entirety but yes in a high percentage of the levels of physical-chemical pollutants among a 9 to 60% and microbiological among a 22 to 93%.